2014
DOI: 10.1051/0004-6361/201322107
|View full text |Cite
|
Sign up to set email alerts
|

CFBDS J111807-064016: A new L/T transition brown dwarf in a binary system

Abstract: Binary systems with a substellar companion are quite rare and provide interesting benchmarks. They constrain the complex physics of substellar atmospheres, because several physical parameters of the substellar secondary can be fixed from the much better characterized main-sequence primary. We report the discovery of CFBDS J111807-064016, a T2 brown-dwarf companion to 2MASS J111806.99-064007.8, a low-mass M4.5-M5 star. The brown dwarf was identified from the Canada France Brown Dwarf Survey. At a distance of 50… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 67 publications
1
1
0
Order By: Relevance
“…Figure 1 shows the spectral type distribution of our sample, featuring a clear deficit at early-T spectral types. This deficit was predicted by evolutionary models (e.g., Saumon & Marley 2008, hereinafter SM08) and seen in previous photometrically-selected samples (Burgasser 2007a;Metchev et al 2008;Reid et al 2008b;Marocco et al 2015;Best et al 2018), and is now confirmed in our volume-limited sample, indicating that brown dwarfs cool through these spectral types (T eff ≈ 1400 − 1100; Luhman et al 2007;Cushing et al 2008;Stephens et al 2009;King et al 2010;Deacon et al 2012a,b;Reylé et al 2014;Filippazzo et al 2015;Deacon et al 2017a; in a relatively short time. We also note an uneven distribution of L0-L5 dwarfs whose origin is unclear given that our sample is 90% complete at these types (Section 2.3).…”
Section: The Samplesupporting
confidence: 86%
“…Figure 1 shows the spectral type distribution of our sample, featuring a clear deficit at early-T spectral types. This deficit was predicted by evolutionary models (e.g., Saumon & Marley 2008, hereinafter SM08) and seen in previous photometrically-selected samples (Burgasser 2007a;Metchev et al 2008;Reid et al 2008b;Marocco et al 2015;Best et al 2018), and is now confirmed in our volume-limited sample, indicating that brown dwarfs cool through these spectral types (T eff ≈ 1400 − 1100; Luhman et al 2007;Cushing et al 2008;Stephens et al 2009;King et al 2010;Deacon et al 2012a,b;Reylé et al 2014;Filippazzo et al 2015;Deacon et al 2017a; in a relatively short time. We also note an uneven distribution of L0-L5 dwarfs whose origin is unclear given that our sample is 90% complete at these types (Section 2.3).…”
Section: The Samplesupporting
confidence: 86%
“…The only object in our sample whose L bol was not derived from these three approaches is CFBDS J111807 − 064016, for whichReylé et al (2014) interpolated theBaraffe et al (2003) evolutionary models using the age of the primary star and the object's T eff derived from atmospheric models(Allard et al 2012(Allard et al , 2013 to compute the L bol .…”
mentioning
confidence: 99%